Oscillating improvisation: how entrepreneurial firms create success in foreign market entries over time - Bingham, Christopher B. (Strategic Entrepreneurship Journal, 2009)
Abstract This study explores how entrepreneurial firms become successful in foreign market entries over time. The setting is the foreign market entries of entrepreneurial firms with headquarters in Singapore, the U.S., and Finland. There are several findings. Firms with more successful foreign market entries decrease improvisation in opportunity selection but increase improvisation in opportunity execution. In contrast, firms with less successful foreign market entries do the opposite. Intriguingly, data suggest that increased improvisation in opportunity execution may be influenced by decreased improvisation in opportunity selection, whereas decreased improvisation in opportunity execution may be influenced by increased improvisation in opportunity selection. Overall, besides contributing fresh insights about the relationship between improvisation and performance in new venture firms, a central contribution of this study is shedding light on the texture of entrepreneurial cognition and the little known relationship between cognition, action, amended cognitions, and redirected action. Copyright © 2009 Strategic Management Society.